Echocardiographic characteristics of cardiac myxoma. (14th October 2021) - Koritnik, P; Pavsic, N; Bervar, M; Prokselj, K
Abstract: Background: Accurate imaging differentiation of various cardiac masses is pivotal due to differences in clinical management and treatment. The most common primary cardiac tumor is cardiac myxoma (CM), which is typically located in the left atrium attached to the interatrial septum. Although benign, serious clinical manifestations may occur and surgical treatment of CM is warranted in most cases. Echocardiography is the most common imaging modality, with a reported sensitivity of 90–96%, however accurate diagnosis can be challenging due to the heterogeneous morphological presentation of CM. Purpose: The aim of this study was to determine the utility of echocardiography in CM diagnosis. Methods: We retrospectively analyzed the echocardiographic and pathohistological findings of all consecutive patients admitted to our cardiology department for possible CM between 2005 and 2020. Results: During the 15-year period, 73 patients were admitted for diagnostic evaluation of a possible CM. Subsequently, 54 patients (74%) were diagnosed with CM or another non-myxomal (NM) cardiac tumor, while in others cardiac masses of other etiologies (thrombus, infective endocarditis, etc.) were diagnosed (Figure 1). All but one patient with CM or NM cardiac tumor were treated surgically at our institution and pathohistological specimens were obtained from the resected tumor. There was a significant female preponderance (n=34, 63%) and the mean age at the time of surgery was 64±14 years. Based on the preoperative echocardiographic findings, 45 (85%) tumors were diagnosed as CM and 8 as NM cardiac tumors (Figure 1). Evaluation of pathohistological specimens revealed CM in 39 of 53 (74%) operated patients. Patohistiologically, a NM cardiac tumor was diagnosed in 7 patients who were preoperatively classified as CM. The sensitivity and specificity of preoperative echocardiography for the detection of CM were 97% and 50%, respectively (Figure 1). The echocardiographic characteristics of pathohistologically confirmed CM were compared to cases of NM cardiac tumors. The comparison between the two groups revealed statistically significant differences in localization and tumor size. All NM cardiac tumors were located in an atypical position and 72% of CM were found in a typical position within the left atrium (p<0.001). NM cardiac tumors were also significantly smaller than CM (25.1±12.6 mm vs. 37.5±18.5 mm, p=0.029). Conclusion: Our single-center study confirms the excellent sensitivity of echocardiography for CM diagnosis. The specificity of echocardiography was modest, thus caution is warranted due to a wide differential diagnosis of CM. The diagnosis of CM seems to be less likely with atypical tumor location and small tumor size. Other non-invasive imaging modalities such as cardiac computed tomography or magnetic resonance imaging should be considered in such cases. Funding Acknowledgement: Type of funding sources: None.